(untitled) (Revista de Ciências Agroveterinárias, 2006)
This study care for the medicinal plants most used by the popular healers of Amapá’s State and has as objective to identify and to select the ten plants most indicated by them. Stresses the therapeutic use with popular indications of these plants, demonstrating the common utilization among communities to treat diseases of interest in public health. It opted by the exploratory quantitative method, with reading and collecting data of the 41 healers’ popular meetings, interviewed in year of 1998. It ascertained that the ten medicinal plants most indicated popularly for therapeutic use, of healers’ popular domain, in its majority has the same indication of the scientific community indications favoring the treatments employed by these curators. It concludes that the use of the medicinal plants remains among communities, especially, the ones that live distant of a center that give them support in the health matters, and that tends to grow, with the adiversities faced by the services of official health.